Political developments in Egypt and the role of the military council with the transitional period (2011-2012) - Nasser Zane El Abidine; Shahd Salim Fazaa (Tikrit Journal For Political Science, 2024)
period and beyond، as it carried out a series of measures to keep pace with events، the most important of After the revolution of January 25، 2011، the military institution played a major role، through the Supreme Council of the Armed Forces، in influencing the political scene during the transitional which was working on constitutional amendments and holding presidential elections that resulted in The victory of the first civilian president in the history of Egypt، and the return of the Muslim Brotherhood movement to the forefront of the political scene in Egypt.